Development of High Quality No Fine Concrete - Devi, Dr. G. Nandini (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2016)
Natural sand is being extorted at an increasing rate. Construction industry is looking for an alternative material for sand and research is going on to find new innovative concrete. No fines concrete has been generally used for paving applications, other non-structural application, such as reinforced panels, acoustic, thermal and permeability properties because of its previous nature. In this work, 12.5mm size coarse aggregate is used in place of usually used 20mm size in no fine concrete with various mix ratio of cement and 12.5mm coarse aggregate. Specimens were casted and tested for its mechanical properties. Results are compared with M25 conventional concrete.